Law and Urban Planning. Current problems in the planning of Metropolitan Lima - Ortiz Sánchez, Iván (2020)
Although urban legislation is fundamental to improve the living conditions of Peruvian cities, in the case of Metropolitan Lima the regulatory framework for urban planning is, to say the least, chaotic and ineffective. For this reason, in this paper we describe and analyze the regulatory framework of urban development at the metropolitan level with the objective that the legibility of the regulations helps to improve the design of public policies and guidelines for the planning of the city. Through cabinet analysis, workshops and unstructured interviews, we studied the history, actors and instruments of the urban planning regulatory framework of Metropolitan Lima. We conclude that this legal framework currently faces critical challenges such as administrative fragmentation and lack of vision of the city, institutional weakness and the lack of systematicity in the regulations.